Contrast-enhanced ultrasound in the diagnosis of head and neck squamous cell carcinoma - G. F. Allakhverdieva; G. T. Sinyukova; T. Yu. Danzanova; E. V. Kovaleva; O. A. Saprina; E. A. Gudilina (Опухоли головы и шеи, 2019)
The study objective is to evaluate the capacity of contrast-enhanced ultrasound in the diagnosis of head and neck squamous cell carcinoma.Materials and methods. We examined 34 patients with head and neck tumors (or suspected of having a tumor) using contrast-enhanced ultrasound imaging with sulfur hexafluoride.Results. Contrast enhancement of primary and recurrent tumors (developed within 3 months since the end of treatment) was characterized by rapid wash-in (including peak enhancement) and wash-out of contrast agent. However, recurrent tumors (developed within 3 months after treatment) demonstrated slightly slower wash-in than primary tumors. In patients with suspected relapse, which was not confirmed by histological examination, contrast agent accumulated only in the surrounding tissues and did not penetrate into the fibrous infiltrate; there were no wash-in and wash-out phases (although this did not exclude the presence of small tumors in the infiltrate). By contrast, tumors demonstrated rapid achievement of peak enhancement and fast wash-out. Laryngeal and laryngopharyngeal tumors accumulate and release contrast agent like any other oropharyngeal squamous cell carcinomas. Laryngeal cartilages have high echogenicity and don’t accumulate contrast agent. Tumor-altered vocal cords accumulate contrast agent, which significantly improves the visualization. Intact vocal cords appear as hyperechogenic symmetric structures on B-scans. Contrast-enhanced ultrasound imaging allows better visualization of the vocal cords. Contrast-enhancement can significantly improve the diagnostic value of ultrasound examination of the larynx, especially when B-scanning is hindered by some anatomical features (such as large Adam’s apple) or ossification of laryngeal cartilages.Conclusion. Contrast-enhanced ultrasound imaging of the head and neck is a highly promising diagnostic tool, although it requires further evaluation. Improved visualization with contrast-enhancement increases the diagnostic value of the method for the differentiation between various tumors and fibrotic changes and detection of tumor spread to the laryngeal cartilages, which is important for surgical treatment and planning anticancer therapy.